Political-Economic Instability in Latin America and Its Impact on Gender Inequality in Science - Pradier, Carolina; Kozlowski, Diego; S. Shokida, Natsumi; Larivière, Vincent (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Technology and business administration are different concepts but they are closely related nowadays and it is important to know the benefits that this combination can bring in the labor field. Thus, technology has a fundamental role in the daily work of a company and its good use brings important benefits. This is how the present work showed the benefits that are closely related to the efficiency and effectiveness of companies.